2022
DOI: 10.1073/pnas.2118675119
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic dual conversion reactions assisting Pb-S electrochemistry for energy storage

Abstract: Significance Based on the analysis of three thermodynamic parameters of various M-S systems (solubility of metal sulfides [M x S y ] in aqueous solution, volume change of the metal-sulfur [M-S] battery system, and the potential of S/M x S y cathode redox couple), an aqueous Pb-S battery operated by synergistic dual conversion reactions (cathode: S⇄PbS, anode: Pb 2+ ⇄PbO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Elemental sulfur features top-level specific capacity (typically >1000 mAh g −1 ) via two-electron transfer reactions. In studies of SABs, aqueous metal-sulfur batteries, including Cu-S [ 9–11 ], Fe-S [ 12 ], Zn-S [ 13 , 14 ], Pb-S [ 15 ], Ca-S [ 16 ], Li-S [ 17 ] and Na-S [ 18 ], have attracted much recent attention due to their high actual specific capacity in aqueous electrolytes. Despite some impressive results so far, the electrically insulated elemental sulfur (5 × 10 −30 S cm −1 ) inevitably undergoes a distinct volume expansion of at least ∼50% during discharging, accompanied by the conversion of dense S 8 (1.96 g cm −3 ) to M x S y (such as Li 2 S, Cu 2 S, and PbS) [ 19 ], leading to kinetics and reversibility limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Elemental sulfur features top-level specific capacity (typically >1000 mAh g −1 ) via two-electron transfer reactions. In studies of SABs, aqueous metal-sulfur batteries, including Cu-S [ 9–11 ], Fe-S [ 12 ], Zn-S [ 13 , 14 ], Pb-S [ 15 ], Ca-S [ 16 ], Li-S [ 17 ] and Na-S [ 18 ], have attracted much recent attention due to their high actual specific capacity in aqueous electrolytes. Despite some impressive results so far, the electrically insulated elemental sulfur (5 × 10 −30 S cm −1 ) inevitably undergoes a distinct volume expansion of at least ∼50% during discharging, accompanied by the conversion of dense S 8 (1.96 g cm −3 ) to M x S y (such as Li 2 S, Cu 2 S, and PbS) [ 19 ], leading to kinetics and reversibility limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Making such primary batteries rechargeable is apparently a good way to achieve higher energy secondary batteries, which is always a formidable challenge. [4][5][6][7][8][9][10] Very recently, the Dai group tackled this oxidized to form Br 2 , which is the main source of the reversible capacity. Overall, the K/Br battery in this work operates via redox reactions between Br 2 /Br − at the HCS cathode and K + /K at the K-metal anode, making it rechargeable.…”
Section: Introductionmentioning
confidence: 99%
“…Making such primary batteries rechargeable is apparently a good way to achieve higher energy secondary batteries, which is always a formidable challenge. [ 4–10 ] Very recently, the Dai group tackled this thorny problem and realized the rechargeability of Na (or Li)/SOCl 2 batteries for the first time. [ 11,12 ] Based on the primary chemistry of SOCl 2 reduction, the authors demonstrated that the transformation of NaCl film (produced in the initial discharge) to Na and Cl 2 was the main reaction during charging.…”
Section: Introductionmentioning
confidence: 99%
“…The large requirement for storing renewable energy from solar or wind calls for safe, low‐cost, and high‐performance rechargeable batteries [1–3] . Traditional lithium ion batteries are qualified for this practical application but encounter the scarcity of lithium minerals and the increasing price [4–8] .…”
Section: Introductionmentioning
confidence: 99%